2008
DOI: 10.1177/1049909107312595
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Perceptions of Hospice Palliative Care Volunteers

Abstract: A total of 50 nurses (hospital and home care) responded to a survey designed to measure: (1) their attitudes toward, and knowledge of, hospice palliative care volunteers; (2) the types of tasks they felt it was appropriate for volunteers to perform; and (3) how valuable they felt different members of the hospice palliative care team are. In addition, they were asked to respond to some open-ended questions (eg, "Do you feel that it is appropriate for hospice palliative care volunteers to know patient medical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 21 publications
1
55
0
3
Order By: Relevance
“…[7][8][9] Other members of the formal caregiving team also recognize the importance of the volunteers' role. For example, in one American study, 24 of the 25 hospice employees (nurses and social workers) surveyed believed that volunteers were ''a vital part of hospice'' 10(p128) and 75% of the nurses surveyed by Claxton-Oldfield, Hastings, and Claxton-Oldfield 11 believed that volunteers make their work easier. Given the absolutely essential role of volunteers in hospice palliative care, one critical issue concerns the recruitment and retention of volunteers.…”
mentioning
confidence: 97%
“…[7][8][9] Other members of the formal caregiving team also recognize the importance of the volunteers' role. For example, in one American study, 24 of the 25 hospice employees (nurses and social workers) surveyed believed that volunteers were ''a vital part of hospice'' 10(p128) and 75% of the nurses surveyed by Claxton-Oldfield, Hastings, and Claxton-Oldfield 11 believed that volunteers make their work easier. Given the absolutely essential role of volunteers in hospice palliative care, one critical issue concerns the recruitment and retention of volunteers.…”
mentioning
confidence: 97%
“…[6][7][8]10,11 The wide role that the CVW undertakes has been shown to be beneficial and includes both physical and non-physical care.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] It is also reported that the presence of volunteers helps the staff and they are referred to as providing an invaluable resource. 7,9 However, in developing countries the role of the palliative care volunteer is very different and is, in the main, community-based. In India, the Neighbourhood Network in Palliative Care (NNPC) developed in Kerala is an attempt to develop a sustainable community-owned service that can offer long-term care and palliative care.…”
Section: Palliative Care Volunteersmentioning
confidence: 94%
See 1 more Smart Citation
“…9 Some hospice palliative care volunteers provide, free of charge, services of a professional nature (eg, language translator, lawyer, Reiki practitioner, beautician), while others prefer to engage in nondirect patient/family care tasks. These administrative volunteers might work in the volunteer program's office and help with typing, filing, answering phones, and so on.…”
mentioning
confidence: 99%